MiR-367-3p Alleviates Oxidative Stress Injury in the Ischemia/Reperfusion Injury Cell Model by Targeting Nicotinamide Adenine Dinucleotide Phosphate Oxidase 4-mediated Keap1/Nrf2/ARE Pathway - Qian He; Xingwen Tian; Yujie Zhang; Qiong Mu (Journal of Physiological Investigation)
Ischemic stroke is a debilitating central nervous disease linked to oxidative stress. Although miR-367-3p has been reported to be related to ischemic stroke, the direct evidence concerning oxidative stress remains elusive. Our study aimed to elucidate the mechanisms associated with oxidative stress in ischemic stroke. Initially, we discovered that miR-367-3p was notably downregulated in SH-SY5Y cells induced by oxygen-glucose deprivation/reoxygenation (OGD/R). Employing the in vitro ischemia/reperfusion injury model, we further demonstrated that overexpression of miR-367-3p alleviated OGD/R-induced apoptosis, inflammation, and oxidative stress, accompanied by the activation of the Keap1/Nrf2/ARE pathway. Mechanistically, nicotinamide adenine dinucleotide phosphate oxidase 4 (NOX4) was confirmed to be the target of miR-367-3p by dual-luciferase reporter assay. Moreover, the knockdown of NOX4 mimicked, while overexpression reversed the effects of miR-367-3p overexpression on OGD/R-induced oxidative stress injury and the impaired Keap1/Nrf2/ARE pathway. In conclusion, our findings indicate that miR-367-3p mitigates OGD/R-induced oxidative stress injury by activating the Keap1/Nrf2/ARE pathway through targeting NOX4.